Geschichte der Heimat Zur Genese ihrer Semantik in Literatur, Religion, Recht und Wissenschaft - Oesterhelt, Anja (Studien und Texte zur Sozialgeschichte der Literatur, 2021)
This study reconstructs the term and concept of "home," from its traceable origins until the early twentieth century.Literature, here, has acted as a continuous point of reference for the German discursive fields of religion, law, pedagogy, and ethnology: as a medium for the affirmation, confusion, and passing on of social ideas, as well as a site where discourse is constructed and the semantics of home readjusted.